Phosphodiesterase 8B gene variants are associated with serum TSH levels and thyroid function - Arnaud-Lopez, Lisette; Usala, Gianluca; Ceresini, Graziano; Mitchell, Braxton D; Pilia, Maria Grazia; Piras, Maria Grazia; Sestu, Natascia; Maschio, Andrea; Busonero, Fabio; Albai, Giuseppe; Dei, Mariano; Lai, Sandra; et al. (American journal of human genetics, 2008)
Thyroid-stimulating hormone (TSH) controls thyroid growth and hormone secretion through binding to its G protein-coupled receptor (TSHR) and production of cyclic AMP (cAMP). Serum TSH is a sensitive indicator of thyroid function, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over a life span. By genotyping 362,129 SNPs in 4,300 Sardinians, we identified a strong association (p = 1.3 x 10(-11)) between alleles of rs4704397 and circulating TSH levels; each additional copy of the minor A allele was associated with an increase of 0.13 muIU/ml in TSH. The single-nucleotide polymorphism (SNP) is located in intron 1 of PDE8B, encoding a high-affinity cAMP-specific phosphodiesterase. The association was replicated in 4,158 individuals, including additional Sardinians and two genetically distant cohorts from Tuscany and the Old Order Amish (overall p value = 1.9 x 10(-20)). In addition to association of TSH levels with SNPs in PDE8B, our genome scan provided evidence for association with PDE10A and several biologically interesting candidates in a focused analysis of 24 genes. In particular, we found evidence for association of TSH levels with SNPs in the THRB (rs1505287, p = 7.3 x 10(-5)), GNAQ (rs10512065, p = 2.0 x 10(-4)), TG (rs2252696, p = 2.2 x 10(-3)), POU1F1 (rs1976324, p = 3.9 x 10(-3)), PDE4D (rs27178, p = 8.3 x 10(-3)), and TSHR (rs4903957, p = 8.6 x 10(-3)) loci. Overall, the results suggest a primary effect of PDE8B variants on cAMP levels in the thyroid. This would affect production of T4 and T3 and feedback to alter TSH release by the pituitary. PDE8B may thus provide a candidate target for the treatment of thyroid dysfunction.